Incubation success and habitat selection of shore‐spawning kokanee Oncorhynchus nerka: effects of water‐level regulation and habitat characteristics. Issue 3 (28th June 2014) - Whitlock, Steven L.; Quist, Michael C.; Dux, Andrew M.
Abstract Changes to water‐level regimes have been known to restructure fish assemblages and interfere with the population dynamics of both littoral and pelagic species. The effect of altered water‐level regimes on shore‐spawning kokanee Oncorhynchus nerka incubation success was evaluated using a comprehensive in situ study in Lake Pend Oreille, ID, USA. Survival was not related to substrate size composition or depth, indicating that shore‐spawning kokanee do not currently receive a substrate‐mediated survival benefit from higher winter water levels. Substrate composition also did not differ among isobaths in the nearshore area. On average, the odds of an egg surviving to the preemergent stage were more than three times greater for sites in downwelling areas than those lacking downwelling. This study revealed that shoreline spawning habitat is not as limited as previously thought. Downwelling areas appear to contribute substantially to shore‐spawning kokanee recruitment. This research illustrates the value of rigorous in situ studies both for testing potential mechanisms underlying population trends and providing insight into spawning habitat selection.